The Λ and the CDM as Integration Constants - Priidik Gallagher (MDPI AG, 2021)
Notoriously, the two main problems of the standard <semantics>Λ</semantics>CDM model of cosmology are the cosmological constant <semantics>Λ</semantics> and the cold dark matter, CDM. This essay shows that both the <semantics>Λ</semantics> and the CDM arise as integration constants in a careful derivation of Einstein’s equations from first principles in a Lorentz gauge theory. The dark sector of the universe might only reflect the geometry of a spontaneous symmetry breaking that is necessary for the existence of spacetime and an observer therein.